1992
DOI: 10.1093/oxfordjournals.humrep.a137824
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase IV as a differentiation marker of the human endometrial glandular cells

Abstract: To investigate the involvement of membrane-bound peptidases in the human endometrial function, we examined the expression of dipeptidyl peptidase (DPP) IV and its enzyme activity. Immunohistological studies revealed that DPP IV was detected on human endometrial glandular cells and endometrial surface epithelium, but not on endometrial stromal cells or decidual cells in the first trimester of pregnancy. DPP IV expression on glandular cells and surface epithelium was weak in the proliferative phase, began to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…In addition, we found that another membrane-bound aminopeptidase, dipeptidyl peptidase-IV (DPP-IV, EC.3.4.14.5), is expressed on human luteal cells and endometrial glandular cells Imai et al, 1992cImai et al, , 1996. DPP-IV is specific for removing X amino acid (an unspecified amino acid, Xaa)-Pro or -Ala dipeptides from the N-termini of polypeptides and proteins (Flentke et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that another membrane-bound aminopeptidase, dipeptidyl peptidase-IV (DPP-IV, EC.3.4.14.5), is expressed on human luteal cells and endometrial glandular cells Imai et al, 1992cImai et al, , 1996. DPP-IV is specific for removing X amino acid (an unspecified amino acid, Xaa)-Pro or -Ala dipeptides from the N-termini of polypeptides and proteins (Flentke et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are consistent with this expectation. CD26 is the equivalent of the ectopeptidase dipeptidyl peptidase IV [4,5,12] . The alpha chains of human chorionic gonadotropin and sheep prolactin are among the substrates of this enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The alpha chains of human chorionic gonadotropin and sheep prolactin are among the substrates of this enzyme. The human chorionic gonadotropin alpha chain is also a component of follicle-stimulating hormone and luteinizing hormone [12,26,27] . So, the existence of CD26 is very probable in endometrium and decidua.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations